Effect of the Ethanolic Extract of the Rhizome of Gastrodia elata on Spermatogenesis in Male Sprague-Dawley Rats - Wei, Chai Zi; Jun, Chuah Jia; Parasuraman, Subramani (Free Radicals and Antioxidants, 2026)
Background: Gastrodia elata is a traditional Chinese herb used to treat neurological disorders. Gastrodin, its main bioactive component, has been extensively studied for pharmacological effects. This study aimed to evaluate the effect of the Ethanolic Extract of the rhizome of G. elata (EEGE) on spermatogenesis in male Sprague Dawley (SD) rats. Materials and Methods: The rhizome powder was extracted with ethanol. Healthy adult male SD rats were divided into six groups (n=6 per group) and treated daily for 28 days, viz., Control, Vitamin C (200 mg/kg), EEGE (100, 200, 400, and 800 mg/kg). Post-treatment, bilateral orchiectomy was performed, and sperm count and motility were assessed. Blood samples were collected at the end of the study for biochemical and haematological analyses. After sacrifice, the liver, kidneys, and testes were excised and weighed for organ weight analysis. Results: EEGE treatment significantly affected some liver function and haematological parameters compared to the control. No significant changes were observed in body weight, kidney function, lipid profile, electrolytes, sperm motility, or sperm count across EEGE-treated and Vitamin C groups. Conclusion: EEGE exhibited no adverse effects on body weight, renal function, or spermatogenesis in male SD rats; higher doses affected liver enzyme levels and some haematological parameters.
Keywords: Liver enzymes; Reproductive toxicity; Sperm count; Spermatogenesis